2019
DOI: 10.1002/jmd2.12036
|View full text |Cite
|
Sign up to set email alerts
|

The Mini Mental State Examination does not accurately screen for objective cognitive impairment in Fabry Disease

Abstract: Fabry disease (FD) patients may suffer from objective cognitive impairment (OCI). This study assessed the accuracy of the Mini Mental State Examination (MMSE) to screen for OCI in FD patients. Presence or absence of OCI was established using a neuropsychological test battery. For different MMSE cutoffs sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and clinical utility index (CUI) to identify OCI were calculated. Eighty‐one patients were included (mean age 44.5 ± 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Therefore MoCA should be preferred to MMSE in populations at risk for MCI or with early-stage dementia. In a study conducted by Körver S, et al MoCA questionnaire classified 21% of patients with FD as having MCI, compared with 11% in the reference group (14). These data are consistent with our results.…”
Section: Wwwirdrjournalcomsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore MoCA should be preferred to MMSE in populations at risk for MCI or with early-stage dementia. In a study conducted by Körver S, et al MoCA questionnaire classified 21% of patients with FD as having MCI, compared with 11% in the reference group (14). These data are consistent with our results.…”
Section: Wwwirdrjournalcomsupporting
confidence: 92%
“…The most commonly used screening test in the diagnosis of cognitive impairment is MMSE. Körver S, et al showed that MMSE did not allow screening for MCI in patients with FD and it may lose its predictive value when the cognitive impairment is milder, less prevalent and occurs predominantly in the executive domain, as appears to be the case in FD (14). Our results are consistent with the finding that MMSE cannot accurately distinguish patients with subtle cognitive impairment from patients without clinically detectable cognitive impairment.…”
Section: Wwwirdrjournalcomsupporting
confidence: 88%
See 1 more Smart Citation
“…Early diagnosis of CI can contribute to specific clinical classification and prognosis and progression of the disease, as well as to treatment. The mini-mental state examination (MMSE) and Montreal Cognitive Assessment (MOCA) were general screening tools for CI [ 7 , 8 ], these tools have proven to be highly sensitive [ 9 ]. However, both age and education level affect MMSE scores [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies that have investigated the cognitive functioning of older South Korean adults have classified cognitive status using Korean versions of the Mini Mental Status Examination (MMSE; Park & Yoo, 2002). While the MMSE, including its Korean variations, is widely used as a screening tool for cognitive impairment (Mole & Demeyere, 2020), it has been criticized for having poor accuracy in diagnosing mild cognitive impairment and dementia (Körver et al., 2019). A potential solution is to use a combination of cognitive function measured by the K‐MMSE and difficulties in instrumental activities of daily living (IADL; Luttenberger et al., 2012; Mejia‐Arango & Gutierrez, 2011).…”
Section: Introductionmentioning
confidence: 99%